A rapid, sensitive high performance liquid chromatographic method for the determination of meropenem in pharmaceutical dosage form, human serum and urine - KÜÇÜKGÜZEL, İLKAY (JOHN WILEY & SONS LTD, 2001)
A new, simple, precise and rapid high performance liquid chromatographic method was developed for the determination of meropenem in human serum, urine and pharmaceutical dosage forms. Chromatography was carried out on an LC18 column using a mixture of 15 mM KH2PO4:acetonitrile:methanol (84:12:4; v/v/v), adjusted to pH 2.8 with H3PO4 The proposed method was conducted using a reversed-phase technique, UV monitoring at 307.6 nm and cefepime as an internal standard. The: retention times were 5.98 and 7.47 min for cefepime and meropenem, respectively. The detector response was linear over the concentration range of 50-10,000 ng/mL. The detection Limit of the procedure was found to be 22 ng/mL. The detection limit for meropenem in human plasma was 108.4 ng/mL and the corresponding value in human urine was 179.3 ng/mL. No interference from endogenous substances in human serum, urine and pharmaceutical preparation was observed. The proposed method is sufficiently sensitive for determination of the concentrations of meropenem and may have clinical application for its monitoring in patients receiving the drug. Copyright (C) 2001 John Wiley & Sons, Ltd.